Digital fascism - Fuchs, Christian 1976- (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2022)
This fourth volume in Christian Fuchs's Media, Communication and Society book series outlines the theoretical foundations of digital fascism and presents case studies of how fascism is communicated online. Digital Fascism presents and engages with theoretical approaches and empirical studies that allow us to understand how fascism, right-wing authoritarianism, xenophobia, and nationalism are communicated on the Internet. Divided into three parts, the book builds on theoretical foundations from key theorists such as Theodor W. Adorno, Franz L. Neumann, Erich Fromm, Herbert Marcuse, Wilhelm Reich, Leo Löwenthal, Moishe Postone, Günther Anders, M.N. Roy, Henry Giroux, and Martin Heidegger. The second part draws on a range of case studies, including Nazis celebrations of Hitler's birthday on Twitter, the 'red scare 2.0' directed against Jeremy Corbyn, Donald Trump, Boris Johnson, and the Austrian presidential election to analyse communication online and in social media. In conclusion, Fuchs argues that slowing down the logic of the media can advance and renew debate culture in the age of digital authoritarianism, fake news, and filter bubbles. Each chapter focuses on a particular dimension of digital fascism or a critical theorist whose work helps us to illuminate how fascism and digital fascism work, making this essential reading for both undergraduate and postgraduate students of media and communication studies, sociology and politics"--Provided by publisher.
Introduction -- The Relevance of Franz L. Neumann's Critical Theory Today: Anxiety and Politics in the New Age of Authoritarian Capitalism -- Günther Anders's Critique of Ideology -- M. N. Roy's Critique of Ideology, Fascism, and Nationalism -- Martin Heidegger's Anti-Semitism: Philosophy of Technology and the Media in the Light of the Black Notebooks. Implications for the Reception of Heidegger in Media and Communication Studies -- Anti-Semitism, Anti-Marxism, and Technophobia: The Fourth Volume of Martin Heidegger's Black Notebooks (1942-1948) -- Fascism 2.0: Hitler's Birthday on Twitter -- Red Scare 2.0: User-Generated Ideology in the Age of Jeremy Corbyn and Social Media. -- Racism, Nationalism and Right-Wing Extremism Online: The 2016 Austrian Presidential Election on Facebook -- A Frankfurt School Perspective on Donald Trump and His Use of Social Media -- Donald Trump and Neoliberal Fascism -- Authoritarian Capitalism, Authoritarian Movements, Authoritarian Communication 13. Why There Are Certain Parallels Between Joachim C. Fest's Hitler-Biography and Michael Wolff's Trump-Book -- How Did Donald Trump Incite a Coup Attempt? -- Boris Johnson Takes His Brexit Demagoguery to the Social Media Sphere -- Slow Media: How to Renew Debate in the Age of Digital Authoritarianism -- Conclusion: What is Digital Fascism?
Includes bibliographical references and index.
Keywords: Fascism; Digital media -- Political aspects; Communication in politics -- Technological innovations; Internet -- Political aspects